Decision model innovation for competitive productivity (CP) in the airport industry. Issue 9 (7th June 2021) - Rengarajan, Srinath; Moser, Roger; Tillessen, Louis; Narayanamurthy, Gopalakrishnan; Reddy, Sai Shiva Jayanth
Abstract : Purpose: The purpose of this paper is to explore the impact of decision model innovation (DMI), set on the decision-making support for the customers, on customer satisfaction and the firm's competitive productivity (FCP). Design/methodology/approach: This study operationalizes the concept of DMI by developing a decision support journey (DSJ) model for the airport industry, using the case of Zurich Airport and its ecosystem. This paper then explores how this DSJ impacts the FCP of Zurich Airport. Findings: This study finds that applying DMI shows potential to improve talent management, resource management and corporate culture, leading to a higher FCP. By centralizing the decision-making process of its customer and decision support, executives gain essential insights into the actual needs of their customers. This enables firms to adapt their products and services to the actual needs of the customer, which leads to higher performance. Research limitations/implications: This study explores the complementarity between DMI and FCP, exploring how operationalizing the concept through DSJ impacts FCP elements, including talent management, resource management and overall corporate culture. This extends extant work on improving non-aeronautical revenues in dynamic environments within airport ecosystems as a converging industry setting. Practical implications: Existing airport digital applications providing minimal support should be expanded to provide an interaction and exchange platform for airport ecosystem players and customers. This paper finds that the firm adopting DMI in the airport/airline industry can set up a win-win situation to achieve competitive productivity by providing decision-making support and valuable insights to its customers. Originality/value: This study is among the first to apply DMI toward improving FCP in the airport industry. It treats airports as an ecosystem of converging industries that can benefit by incorporating customer-focused digitally-enabled solutions to improve decision-making and customer satisfaction.